Analysis of Rainstorm Flood Induced Flash Flood in Wende River Basin - Ma Meihong; Zhou Yue; Bi Shiyao; He Bingshun; Li Qing; Li Ting (E3S Web of Conferences, 2022)
Due to the joint influence of climate and topography, flash flood disasters in the Wende River Basin of Jilin Province occurred repeatedly, causing serious casualties and huge economic losses; in July 2017, three floods with large rainfall intensity and profound influence occurred in a row in the main stream of Wende River. Based on official measured data of the Wende River basin, three typical rainfall processes (“July 13”, “July 20” and “, “August 3 “) are selected to discuss the rainfall characteristics. The triggered characteristics, induced factors and the disaster mechanism of the basin are preliminarily explored from the aspects of rainfall weather system, temporal and spatial distribution of rainstorm and flood, geographical factors to analyze the best countermeasures for flash flood prevention. The above will provide reference for the non-engineering measure project of flash flood prevention currently under construction.